Restoring U. S. Higher Education - Wood, Peter W. (Journal of interdisciplinary studies, 2019)
To restore intellectual freedom, the search for truth, and promotion of virtuous citizenship to American higher education, reformers will have to overcome deeply entrenched intellectual and institutional opposition. The prospects for persuading existing colleges and universities to attempt such a thing are dim. Supporters of the traditional ideals of liberal education have on their side powerful arguments rooted in human nature and civilizational dynamics, but these supporters are marginalized in the academy and contemporary America as a whole. Hope for restoration of the traditional liberal arts, however, may be found in the growing public disenchantment with the price and quality of college education in America. Colleges are closing at an accelerating pace; new technologies and alternative social arrangements are gaining ground; and the higher education establishment is proving unskillful in responding to these challenges. As the turmoil expands, opportunities will open for new approaches. Advocates for a curriculum better rooted in human nature and in the achievements of Western civilization will have a fighting chance to restore perennial ideals and reinvent the undergraduate college.